Herd reconstitution for African livestock keepers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Restocking: a guide: Herd reconstitution for African livestock-keepers as part of a strategy for disaster rehabilitation by Clare Oxby 1994 67pp ISBN 0 9522299 00